FLORA MOSAIC MOTIF ON CASUAL DRESS USING ITAJIME AND ECOPRINT TECHNIQUES - Febriyanti, Afrida Cahya; Asiatun, Kapti (Acintya, 2024)
Flora Mozaik displays the beauty of flowers with six symmetrical petals reinforced by fern leaves, the diversity of round paper mosaics in green color harmony that represents the growth and harmony of nature. The research aims to analyze the market response to fashion products developed through itajime and ecoprint techniques using natural dyes. The research method used in this study is the R&D method with the PPE (Planning, Production, and Evaluation) model to explore floral mosaic motifs on casual dresses using itajime and ecoprint techniques. This R&D research method details the steps in each stage of fashion product development from initial planning to evaluation. The results of the public test showed a positive response from the age group of 19-26 years, towards the fashion products produced through itajime and ecoprint techniques with natural dyes as indicated by the high level of preference (really like and like) of the respondents. This shows that continuous innovation in production technology makes it possible to produce products that are in demand in the market, and the results of the public testing confirmed strong acceptance among the subjects.